Investigating Pathways of Ventilation Induced Brain Injury on Cerebral White Matter Inflammation and Injury After 24 h in Preterm Lambs - Chan, Kyra YY; Tran, Nhi T.; Papagianis, Paris C.; Zahra, Valerie A.; Nitsos, Ilias; Moxham, Alison M.; LaRosa, Domenic A.; McDonald, Courtney; Miller, Suzanne L.; Galinsky, Robert; Alahmari, Dhafer M.; Stojanovska, Vanesa; et al. (Frontiers in Physiology, 2022)
Initiation of respiratory support in the delivery room increases the risk and severity of brain injury in preterm neonates through two major pathways: an inflammatory pathway and a haemodynamic pathway. The relative contribution of each pathway on preterm brain injury is not known. We aimed to assess the role of the inflammatory and haemodynamic pathway on ventilation induced brain injury (VIBI) in the preterm lamb. Fetal lambs (125±1 days gestation) were exteriorised, instrumented and ventilated with a high tidal-volume (VT) injurious strategy for 15 min either with placental circulation intact to induce the inflammatory pathway only (INJINF; n=7) or umbilical cord occluded to induce both the inflammatory and haemodynamic pathways (INJINF+HAE; n=7). Sham controls were exteriorised but not ventilated (SHAM; n=5) while unoperated controls (UNOP; n=7) did not undergo fetal instrumentation. Fetuses were returned in utero following intervention and the ewe allowed to recover. Arterial blood gases and plasma were sampled periodically. Twenty-four hours following intervention, lambs were delivered and maintained on non-injurious ventilation for ~40 min then brains were collected post-mortem for immunohistochemistry and RT-qPCR to assess inflammation, vascular pathology and cell death within white matter regions. Compared to INJINF lambs, INJINF+HAE lambs achieved a consistently higher VT during injurious ventilation and carotid blood flow was significantly lower than baseline by the end of ventilation. Throughout the 24 h recovery period, systemic arterial IL-6 levels of INJINF+HAE lambs were significantly higher than SHAM while there was no difference between INJINF and SHAM animals. At 24 h, mRNA expression levels of pro-inflammatory cytokines, tight junction proteins, markers of cell death, and histological injury indices of gliosis, blood vessel protein extravasation, oligodendrocyte injury and cell death were not different between groups. Injurious ventilation, irrespective of strategy, did not increase brain inflammation or injury 24 h later when compared to control animals. However, the haemodynamic pathway did influence carotid blood flow adaptations during injurious ventilation and increased systemic arterial IL-6 that may underlie long-term pathology. Future studies are required to further characterise the pathways and their long-term effects on VIBI.